Persepsi Guru dalam Implementasi Pendekatan Berdiferensiasi pada Pembelajaran IPAS di Sekolah Dasar - Furkan; Imam Sofian; Sherly Dwi Amelia; Sarif Syahrudin; Sarahturrahmiati; Wildan Ummairah; Muhammad Fajri; Khanif Anwar; Imam Ahyar (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze elementary school teachers’ perceptions of the implementation of differentiated learning in Science and Social Studies (IPAS) within the Merdeka Curriculum. Differentiated learning is regarded as an approach that accommodates students’ readiness, interests, and learning profiles by adjusting learning content, processes, and products. This research employed a quantitative descriptive method using a questionnaire consisting of 40 statements measuring teachers’ knowledge, attitudes, pedagogical competence, and classroom implementation practices. The findings indicate that teachers generally hold positive perceptions regarding the importance of differentiated learning in IPAS, as it is believed to enhance student participation, strengthen inquiry skills, and accommodate diverse learning styles. However, several challenges remain, including limited time for diagnostic assessment, insufficient training on differentiation strategies, lack of adaptive learning resources, and classroom management difficulties arising from heterogeneous student abilities. These findings highlight the need for continuous support from schools and government through professional mentoring, flexible teaching resources, and strengthened teacher collaboration. The study is expected to contribute to the development of policies and instructional practices that are more responsive to students’ learning needs in elementary schools.